2017
DOI: 10.1111/jpi.12402
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine‐induced early cardiovascular effects are mediated by the biological clock and prevented by melatonin

Abstract: Second generation antipsychotics (SGA) are associated with adverse cardiometabolic side effects contributing to premature mortality in patients. While mechanisms mediating these cardiometabolic side effects remain poorly understood, three independent studies recently demonstrated that melatonin was protective against cardiometabolic risk in SGA-treated patients. As one of the main target areas of circulating melatonin in the brain is the suprachiasmatic nucleus (SCN), we hypothesized that the SCN is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…The finding that melatonin receptors are present in human vasculature may suggest a direct role of this molecule in the local control of the cardiovascular disease . In addition, the occurrence of certain acute cardiovascular events such as myocardial infarction and sudden cardiac death is more frequent in the early morning, indicating the possible circadian regulation of melatonin in the heart . Furthermore, patients with coronary artery disease have a low melatonin production rate, closely correlating with the stage of the disease pathology; for example, greater reductions are observed in patients with a higher risk of cardiac infarction and/or sudden death, highlighting the necessity to supplement melatonin in order to reduce the risk of acute cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that melatonin receptors are present in human vasculature may suggest a direct role of this molecule in the local control of the cardiovascular disease . In addition, the occurrence of certain acute cardiovascular events such as myocardial infarction and sudden cardiac death is more frequent in the early morning, indicating the possible circadian regulation of melatonin in the heart . Furthermore, patients with coronary artery disease have a low melatonin production rate, closely correlating with the stage of the disease pathology; for example, greater reductions are observed in patients with a higher risk of cardiac infarction and/or sudden death, highlighting the necessity to supplement melatonin in order to reduce the risk of acute cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that melatonin can protect the heart against ischemia-reperfusion injury (28,29). Other studies also support the protective effects of melatonin against heart failure (30)(31)(32) and drug-induced myocardial injury (33). Notably, melatonin has been shown to protect against LPS-induced mitochondrial impairment and myocardial injury (34,35).…”
Section: Introductionmentioning
confidence: 64%
“…Melatonin provides a strong defense against septic myocardial injury. In addition to the protection against cardiovascular disorders (28)(29)(30)(31)(32)(33), melatonin is reported to protect against sepsis and septic organ dysfunction (5). To be specific, melatonin significantly alleviates LPS-induced liver mitochondrial dysfunction (50), LPS-induced blood-brain barrier disruption (51), and oxidative stress injury in skeletal muscle (52).…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, o atual estudo com indivíduos pinealectomizados é uma excelente prova de conceito por focar nessa população específica.Poucos estudos avaliaram o peso corporal205,236 . Entretanto, alguns dados interessantes decorrem de estudos em situações obesogênicas, como a menopausa ou o início do uso de antipsicóticos[237][238][239][240] . Um pequeno estudo sugeriu que o uso concomitante de fluoxetina com melatonina no período de perimenopausa em mulheres com transtorno da compulsão alimentar periódica (TCAP) levou a uma redução de IMC altamente significativa, de mais de 4 kg/m², comparado com um efeito nulo no grupo apenas em uso de fluoxetina241 .…”
unclassified
“…De forma análoga, um estudo com melatonina unicamente após a menopausa mostrou uma redução de massa gorda e um aumento de massa magra, embora com pequeno efeito sobre o IMC238 . Alguns estudos observaram que a administração de melatonina reduziu de forma significante o ganho de peso e os fatores de risco cardiometabólicos, muito comuns com o uso de antipsicóticos atípicos237,239,240,242,243 .Embora a melatonina seja pouco estudada na regulação metabólica em humanos, ao contrário do que ocorre em animais, como indicado acima, ela tem diversos outros usos clínicos potenciais, muitos com dados robustos e muitos ainda em investigação143,[244][245][246][247][248][249] . A melatonina é empregada em diversos países do mundo como medicação de venda livre sem receita (OTC do inglês over-the-counter) ou como suplemento alimentar sem uma adequada regulação por parte das agências sanitárias249 .…”
unclassified